Developing-country perspectives on Agriculture R&D: New pressures for self-reliance - Alston, Julian M.; Pardey, Philip G. (International Food Policy Research Institute, 2006)
This chapter provides a conceptual and empirical context for the case studies in Chapters 3 through 12. First, we briefly discuss the nature of market failures in agricultural research—both among firms within a country, and among nations—and the roles for government intervention in general. Next, we consider the distinguishing features of less-developed countries and what they might imply for R&D policy. We also discuss the important role of agricultural R&D and technology spillovers among nations, and the past dependence of the world’s poorest countries on their richer neighbors. Next, we document the longer-term global story of institutions and investments in agricultural R&D, emphasizing the great importance of past achievements in agriculture and recent changes that leave grounds for concern about the prospects for the next 20 years and beyond. In the light of these facts, we contemplate the prospects for the future and the implied need to reinvent international collective action in agricultural R&D and reinvest in the associated global public goods institutions.